The Influence of Islamic Bank Products and Services on Customer Satisfaction at Bank Syariah Indonesia in the Ulak Karang Selatan Area, Padang City - Siska Fitrima Sari; Fadilah Ani (The Future of Education Journal, 2025)
This study aims to determine the influence of Islamic banking products and services on customer satisfaction at Bank Syariah Indonesia in the Ulak Karang Selatan area. A quantitative method was employed in this research. The analytical technique used was multiple linear regression analysis. The sample consisted of 98 respondents in the year 2025. The research sample included customers of Bank Syariah Indonesia in the Ulak Karang Selatan area, selected using the Lemeshow formula and a purposive sampling technique. The results of the study indicate that Islamic banking products and services have a positive and significant effect on customer satisfaction at Bank Syariah Indonesia in the Ulak Karang Selatan area.